Disseminated emergomyces orientalis infection in a patient with systemic lupus erythematosus - Luo, Jun; An, Na; Liu, Yarong; Li, Yisheng (Frontiers in Cellular and Infection Microbiology, 2024)
A case of Eimonosis orientalis was reported in a 52-year-old male farmer who presented with cough, phlegm, fever, headache, and nausea for more than 4 days. Haemophilic cells and fungal spores were identified in the bone marrow smear and confirmed as Aemon orientalis by culture. The same bacteria were also isolated from blood cultures